Biofortification in underutilized staple crops for nutrition in Asia and Africa - Pfeiffer, Wolfgang H.; Andersson, Meike S.; Govindaraj, Mahalingam; Parminder, Virk; Cherian, Binu; Illona, Paul; Magezi, Sylvia Ruhweza; Mulambu, Joseph (Asia-Pacific Association of Agricultural Research Institutions, 2018)
Malnutrition is one of the biggest public health challenges of the century with about 2 billion people affected by it globally. Biofortification is the process of breeding micronutrients traits into staple food crops, which is bioavailable to make a positive measurable impact to the population that eats such staples on a daily basis. It is a cost-effective, sustainable strategy and complementary in nature to the existing market interventions. Iron pearl millet, iron beans, vitamin A cassava and orange sweet potato can contribute to increase household nutrition in the Asia and Africa. Over the years evidences gathered by partners in crop breeding, nutrition studies and delivery experiences will help to build the foundation for scaling out further to reach millions who need the most.